Dynamic protein interfaces and conformational landscapes of membrane protein complexes - Kharche, Shalmali A.; Sengupta, Durba (Current Opinion in Structural Biology, 2020)
Dynamic interactions between membrane proteins span a range of spatio-temporal scales and determine several cellular outcomes. Experimental methods in structure determination are able to resolve static protein-protein complexes at the membrane, but lack the resolution required for disordered, flexible domains and dynamic interactions. Computational approaches could bridge the resolution gap and help to unravel molecular details underlying these crucial interactions. Here, we review current approaches to predict dynamic membrane-protein complexes, with a focus on G protein-coupled receptors (GPCRs). Ensemble coarse-grain simulations have captured the conformational heterogeneity of several membrane receptor complexes. In conjunction, the conformational plasticity of protein interfaces especially encompassing unstructured domains is well represented by atomistic simulations. A combined integrative approach will pave the way forward to understand the molecular details of these dynamic complexes.